Atractylenolide III suppresses senescence‐associated secretome via inhibiting cGAS/NF‐κB pathway in hepatic stellate cells. (31st January 2023) - Wu, Hongyan; Wu, Lixia; Xiao, Linxia; Gu, Yaqin; Liu, Hongxia; Zhang, Lihu; Zhang, Mingguang; Qi, Liang
Abstract: Senescence of activated hepatic stellate cells (aHSCs) is a stable growth arrest that is implicated in liver fibrosis regression. Senescent cells often accompanied by a multi‐faceted senescence‐associated secretory phenotype (SASP). Induction of aHSCs senescence by inhibiting SASP may be a potential therapeutic model against hepatic fibrosis. To evaluate the role of atractylenolide III (ATR III) in the development of chemotherapeutic drug‐induced SASPs in hepatic stellate cells. Etoposide‐induced senescent HSC‐LX2 model was established and treated with ATR III at different concentrations (20, 30 and 40 μM). We found that ATR III dose‐dependently enhanced senescence in etoposide‐induced LX2 cells. ATR III dose‐dependently decreased the release and expression of SASP factors (interleukin [IL]‐1α, IL‐1β, IL6 and IL‐8) in senescent cells. ATR III regulated cyclic GMP‐AMP synthase (cGAS)/nuclear factor κ (NF‐κB) signalling to affect SASP expression in senescent cells. The addition of 2'3′ cGAMP counteracted the effect of ATR III. The release of SASP factors in the conditioned medium from senescent cells could affect cell migration, proliferation and contraction through paracrine manner. Our results indicated ATR III could still enter senescence and prevent the production of SASP and its paracrine effects in senescent cells, an effect that may be related to the possible inhibition of cGAS/NF‐κB signalling by ATR III. Our study proves that ATR III may be an effective potential drug against liver fibrosis by promoting aHSC senescence, which can provide a new choice for the future clinical treatment of liver fibrosis. Abstract : Atractylenolide III (ATR III) could still enter senescence and prevent the production of senescence‐associated secretory phenotypes (SASPs) and its paracrine effects in hepatic stellate cells, an effect that may be related to the possible inhibition of cyclic GMP‐AMP synthase (cGAS)/nuclear factor κ (NF‐κB).